The Use of Remote Sensing Data in Mitigating Forest Fire Threats and Its Impact on National Security - Aji Setyo Wibowo (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
Forest fires have emerged as a recurring environmental and national security threat, exacerbated by climate change, deforestation, and unsustainable human activities such as slash-and-burn agriculture. These fires result in ecosystem degradation, biodiversity loss, greenhouse gas emissions, and disruption to health, food security, and local economies. Remote sensing technology, particularly through satellite sensors and drones, offers real-time data for detecting hotspots, tracking smoke dispersion, and assessing post-fire impacts. Tools like MODIS, VIIRS, and Sentinel have proven effective in fire monitoring and mitigation planning. However, limitations in data resolution, weather interference, and policy integration hinder optimal implementation. In Indonesia, the integration of remote sensing into disaster management systems remains fragmented, often resulting in delayed responses and ineffective coordination. Strengthening human resource capabilities, regulatory frameworks, and multi-sector collaboration is essential to leverage this technology fully. Remote sensing thus stands as a critical solution to reduce wildfire risks and their cascading effects on national security, environmental resilience, and public health.